Bacterial infection before and after stent placement in dogs with tracheal collapse syndrome. (24th January 2020) - Lesnikowski, Sylvia; Weisse, Chick; Berent, Allyson; Le Roux, Alexandre; Tozier, Erik
Abstract: Background: Dogs with tracheal stents often have positive airway bacterial cultures. The pathogenicity of these organisms and risk factors for infection have not been investigated. Objective: Describe bacterial infection in dogs with tracheal collapse before and after tracheal stent placement. Animals: Fifty‐three client‐owned dogs. Methods: Retrospective review of medical records of dogs receiving tracheal stents with thoracic radiographs, tracheoscopy, and endotracheal lavage. Results: There was no difference between the overall prevalence of dogs with positive bacterial cultures before (31/38; 82%) or after stent placement (24/31; 77%) ( P = .67). An increased number of geriatric (17/28; 61%) and traditional‐type collapse (TTC) (16/26; 62%) dogs had positive pathogenic airway infections before stent placement, compared to young (8/25; 32%; P = .04) and malformation‐type collapse (MTC) dogs (9/27; 33%; P = .04). After tracheal stent placement, geriatric dogs had a 52% reduction in pathogenic bacteria infection frequency ( P = .02) and dogs with TTC had a 56% reduction in pathogenic bacteria infection frequency ( P = .01). Significant risk factors for pathogenic infection included a history of pneumonia (OR = 3.6; 95% CI, 0.28‐43.36) and cardiac disease (OR = 1.25; 95% CI, 0.16‐9.92) in geriatric dogs, and hepatomegaly in young dogs (OR = 1.5; 95% CI, 0.12‐19.44). Conclusions and Clinical Importance: Tracheal stent placement does not increase the overall rate of pathogenic bacterial infection in dogs with tracheal collapse and can decrease the rate of subsequent pathogenic infections in geriatric dogs and dogs with TTC that require tracheal stenting. Airway culture and cytology should be performed in all dogs undergoing tracheal stent placement.